Liposomal Dexamethasone Reduces A/H1N1 Influenza-Associated Morbidity in Mice - Kwon, Jung Won; Quan, Hailian; Song, Juha; Chung, Hyewon; Jung, Daun; Hong, Jung Joo; Na, Yi Rang; Seok, Seung Hyeok (Frontiers in Microbiology, 2022)
Re-emerging viral threats have continued to challenge the medical and public health systems. It has become clear that a significant number of severe viral infection cases are due to an overreaction of the immune system, which leads to hyperinflammation. In this study, we aimed to demonstrate the therapeutic efficacy of the dexamethasone nanomedicine in controlling the symptoms of influenza virus infection. We found that the A/Wisconsin/WSLH34939/2009 (H1N1) infection induced severe pneumonia in mice with a death rate of 80%, accompanied by significant epithelial cell damage, infiltration of immune cells, and accumulation of pro-inflammatory cytokines in the airway space. Moreover, the intranasal delivery of liposomal dexamethasone during disease progression reduced the death rate by 20%. It also significantly reduced the protein level of tumor necrosis factor-alpha (TNFα), interleukin-1β (IL-1β), IL-6, and the C-X-C motif chemokine ligand 2 (CXCL2) as well as the number of infiltrated immune cells in the bronchoalveolar lavage fluids as compared to the control and free dexamethasone. The liposomal dexamethasone was mainly distributed into the monocyte/macrophages as a major cell population for inducing the cytokine storm in the lungs. Taken together, the intranasal delivery of liposomal dexamethasone may serve as a novel promising therapeutic strategy for the treatment of influenza A-induced pneumonia.